Characterization, pathogenicity and host range analyses of Lasiodiplodia sp. and related species isolated from fruit rot disease of mango in Peninsular Malaysia - Mohd Sattar, Munirah (2017)
Lasiodiplodia species is an important plant pathogen causing fruit rot, a threatening disease for mango fruits in Malaysia. Capability of thespecies to infect during preand post-harvest phases will reduced mango production and creating tremendous losses in country economic. The information regarding pre-harvest fruit rot disease on mango in Malaysia is still lacking, therefore, this study was conducted. During a series of sampling in July 2014 to May 2015 throughout Peninsular Malaysia, the symptom of fruit rot was observed in the Malaysian mango recommended varieties such as Chok Anan (MA224), Harumanis (MA128), Sala and Epel. Thus, the objectives of this study were to isolate and identify fungi species isolated from mango fruit rot disease based on morphological and molecular approaches using internal transcribed spacer (ITS) and β-tubulin gene (BT2) sequence, to determine whether or not Lasiodiplodia, Pseudofusicoccum and Neofusicoccum isolates are pathogenic and to examine the host range of Lasiodiplodia theobromae, Lasiodiplodia pseudotheobromae and Pseudofusicoccum adansoniae as causal pathogens of mango fruit rot disease in selected commercial fruits. There are 26 isolates were purified and successfully identified as Lasiodiplodia theobromae (17 isolates), Lasiodiplodia pseudotheobromae (3 isolates), Pseudofusicoccum adansoniae (5 isolates) and Neofusicoccum parvum (1 isolate). A combined phylogenetic tree was constructed using maximum-likelihood method showed the same species grouped into the same clade. Clade I consisted of L. theobromae, L. pseudotheobromae and N. parvum while Clade II were P. adansoniae species. For the pathogenicity test, all isolates of Lasiodiplodia species inoculated on healthy mango fruit using non-wounded method are pathogenic and showed fruit rot symptom except for L. pseudotheobromae (B1494). Whereas, for P. adansoniae and N. parvum species isolates, only one isolate of P. adansoniae (B1474) produced fruit rot symptom. The most virulent isolate was L. theobromae (A1718) with disease severity index, DSI of 87.50%. To examine virulence of the pathogenic isolates obtained from mango samples on different hosts, each species isolates with highest DSI in pathogenicity test were inoculated on seven commercial fruits such as apple, banana, musk lime, guava, mandarin, pear and sapodilla. The host range study confirmed that L. theobromae, L. pseudotheobromae and P. adansoniae were pathogenic to apple, musk lime, guava, mandarin and sapodilla with varies in disease severity. As conclusion, L. theobromae, L. pseudotheobromae and P. adansoniae were identified and confirmed as pathogens of pre-harvest fruit rots disease on mango in Malaysia. Those three species are also potential pathogen for apple, banana, musk lime, guava, mandarin and sapodilla if dissemination of inoculums were occurred during pre- or post-harvest stages.This study represents the first report of L. pseudotheobromae and P. adansoniae on pre-harvest mango in Peninsular Malaysia associated with fruit rot disease.